SOME DOUBTFUL ELEMENTS OF COST. - Robinson, J. S. (The Accounting Review, 1926)
Abstract The article presents views of the author about a work which appeared in publications of the American Association of University Instructors in Accounting. I pointed out that the term cost, the meaning of which is by no means standardized, is used to refer primarily to three things, money costs, economic costs and business costs. Money cost is the sense in which the term is popularly used. Most persons think of cost in money terms, it is the price that is paid for goods and services. Scholar Alfred Marshall employed the phrase expenses of production to designate such payments. Since cost in this sense is equivalent to the money payments for goods and services, it follows that the total money paid by all consumers for wages, rent, interest, and profits must be equal to prices paid by all consumers for the satisfaction of their wants. Money costs to the consumer essentially represent selling price, or sales, they are what the consumer pays. The concept of economic cost is very different from that of money cost, as the term is used by the average man, whether consumer or producer. Economic cost is subjective, it is cost in terms of labor, exertion, sacrifice, or disutility. Some writers have called it pain cost and it is measured in irksome labor or reluctant waiting.